2023
DOI: 10.3389/fendo.2023.1054674
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of weight loss herbal intervention therapy and lifestyle modifications on obesity and its association with distinct gut microbiome: A randomized double-blind phase 2 study

Abstract: GoalsTo assess the efficacy and safety of Chinese Medicine Prescription “W-LHIT” in subjects with simple obesity, and to explore its potential mechanism of action.MethodsThirty-seven patients aged 18 to 60 from Wei-En hospital (Weifang City, Shandong, China), participated in a double blinded, placebo-controlled study. Subjects were randomly divided into 2 groups, 18 in treatment and 19 in placebo group. The treatment group took the “W-LHIT” capsules for two months, while the control group received placebo caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Five studies were double-blind, parallel randomized clinical trials, and the other two had a crossover design [14][15][16][17]. They were published between 2015/2023 and carried out in three countries: China, South Korea, and Spain.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were double-blind, parallel randomized clinical trials, and the other two had a crossover design [14][15][16][17]. They were published between 2015/2023 and carried out in three countries: China, South Korea, and Spain.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The herbal medicines studied were Moringa oleifera [16], Punica granatum [18,19], Scutellaria baicalensis [20], Schisandra chinensis [17], and weight loss herbal intervention therapy consisting of five Chinese herbal medicines: Ganoderma lucidum, Coptis chinensis, Astragalus membranaceus, Nelumbo nucifera gaertn, and Fructus aurantii (W-LHIT) [14], and white common bean extract (WCBE) [15].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative abundance of Akkermansia muciniphila, another SCFA producer and mucindegrading bacterium, increased during different restriction programmes in five clinical trials [23,92,97,106,116]. As the level of A. muciniphila is inversely correlated with body weight and directly correlated with the weight loss observed in obese patients after CR restrictions and improvements in multiple indicators of cardio-metabolic health [128][129][130][131], it can be proposed as a prognostic tool in the context of predicting CR success. Further studies are needed to confirm this, as the effect was not consistently observed in all trials.…”
Section: The Impact Of Cr Programs On the Gut Microbiota-common Findingsmentioning
confidence: 99%